2013
DOI: 10.12669/pjms.293.3625
|View full text |Cite
|
Sign up to set email alerts
|

Uterine rupture revisited: Predisposing factors, clinical features, management and outcomes from a tertiary care center in Turkey

Abstract: Objective: To determine the predisposing factors, modes of clinical presentation, management modalities and fetomaternal outcomes of uterine rupture cases at a tertiary care center in Turkey. Methodology: A 14-year retrospective analysis of 61 gravid (>20 weeks of gestation) uterine rupture cases between January 1998 to March 2012 was carried out. Results: The incidence of ruptured uteri was calculated to be 0.116%. Persistence for vaginal delivery after cesarean was the most common cause of uterine rupture (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 11 publications
6
21
2
1
Order By: Relevance
“…A high index of suspicion and quick referral of all patients with previous cesarean sections to a well-equipped hospital with facility of surgery and blood can reduce the incidence of rupture. 15 Contrary to our study Anjali et al and Padhey reported more rupture in unscarred uterus 64.9% and 60% respectively as most of their patient had interventions with uterotonics. 6,9 Higher parity is another risk factor for uterine rupture particularly in spontaneous rupture and induction cases.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…A high index of suspicion and quick referral of all patients with previous cesarean sections to a well-equipped hospital with facility of surgery and blood can reduce the incidence of rupture. 15 Contrary to our study Anjali et al and Padhey reported more rupture in unscarred uterus 64.9% and 60% respectively as most of their patient had interventions with uterotonics. 6,9 Higher parity is another risk factor for uterine rupture particularly in spontaneous rupture and induction cases.…”
Section: Discussioncontrasting
confidence: 92%
“…6 Turgut A et al had 34.4% cases with scar repair and total abdominal hysterectomy each, subtotal hysterectomy in his study was done in 31.1%. 15 Maternal mortality occurred in five cases (8.77%) which was more (3/5) in scarred uterus as compare to unscar one (2/5). Our perinatal mortality was 85.9%.…”
Section: Discussionmentioning
confidence: 89%
“…Minor complications like febrile morbidity, urinary and respiratory infections and paralytic ileus were comparable to those in other studies. 20 In the present study only one maternal deaths was recorded. This could be because of the predominance of cesarean scar ruptures which were amenable to early diagnosis and repair.…”
Section: Resultsmentioning
confidence: 54%
“…The region where this study was conducted is known as a relatively low socioeconomic region. Again, delivery at home is common in this region due to insistence of persons on vaginal birth and even labor induction or augmentation at home is performed in a medically unconscientious way (14,15). As a result, persons may present to clinics with several obstetric complications such as ablation or uterine rupture (15).…”
Section: Discussionmentioning
confidence: 99%